The fluorescent protein iLOV as a reporter for screening of high‐yield production of antimicrobial peptides in Pichia pastoris. Issue 7 (21st March 2022) - Kjeldsen, Annemette; Kay, Jack E.; Baxter, Scott; McColm, Stephen; Serrano‐Amatriain, Cristina; Parker, Scott; Robb, Ellis; Arnold, S. Alison; Gilmour, Craig; Raper, Anna; Robertson, Graeme; Fleming, Robert; et al.
Summary: The methylotrophic yeast Pichia pastoris is commonly used for the production of recombinant proteins at scale. The identification of an optimally overexpressing strain following transformation can be time and reagent consuming. Fluorescent reporters like GFP have been used to assist identification of superior producers, but their relatively big size, maturation requirements and narrow temperature range restrict their applications. Here, we introduce the use of iLOV, a flavin‐based fluorescent protein, as a fluorescent marker to identify P. pastoris high‐yielding strains easily and rapidly. The use of this fluorescent protein as a fusion partner is exemplified by the production of the antimicrobial peptide NI01, a difficult target to overexpress in its native form. iLOV fluorescence correlated well with protein expression level and copy number of the chromosomally integrated gene. An easy and simple medium‐throughput plate‐based screen directly following transformation is demonstrated for low complexity screening, while a high‐throughput method using fluorescence‐activated cell sorting (FACS) allowed for comprehensive library screening. Both codon optimization of the iLOV_NI01 fusion cassettes and different integration strategies into the P . pastoris genome were tested to produce and isolate a high‐yielding strain. Checking the genetic stability, process reproducibility and following the purification of the active native peptide are eased by visualization of and efficient cleavage from the iLOV reporter. We show that this system can be used for expression and screening of several different antimicrobial peptides recombinantly produced in P. pastoris . Abstract : The methylotrophic yeast Pichia pastoris is commonly used for production of recombinant proteins at scale, but identification of an optimally over‐expressing strain following transformation can be time and reagent consuming. Here we introduce the use of iLOV, a flavin based fluorescent protein, as a removable fluorescent marker to identify P. pastoris jackpot strains easily and rapidly. We show that this system can be used for expression, screening, and monitoring of genetic stability and process reproducibility of several different antimicrobial peptides recombinantly produced in Pichia .